Palladium‐Catalyzed Asymmetric Hydrogenolysis of Aryl Triflates for Construction of Axially Chiral Biaryls - Li, Xiang; Wang, Gao‐Wei; Liu, Li‐Xia; Yu, Chang‐Bin; Zhou, Yong‐Gui (Angewandte Chemie International Edition, 2023)
Here we report the first palladium‐catalyzed asymmetric hydrogenolysis of readily available aryl triflates via desymmetrization and kinetic resolution for facile construction of axially chiral biaryl scaffolds with excellent enantioselectivities and s selectivity factors. The axially chiral monophosphine ligands could be prepared from these chiral biaryl compounds and were further applied to palladium‐catalyzed asymmetric allylic alkylation with excellent ee values and high branched and linear ratio, which demonstrated the potential utility of this methodology. We have developed the first palladium‐catalyzed asymmetric hydrogenolysis of aryl triflates through desymmetrization and kinetic resolution that allows the facile construction of axially chiral biaryl scaffolds with excellent results. These chiral compounds could be further converted into chiral monophosphine ligands, which were then used in asymmetric allylic alkylation to produce the desired product with high regio‐ and enantioselectivities.